Manufacturing, Characterisation and Prop erties of Advanced Nanocomposites - Rehan Umer (Ed.); Alokesh Pramanik (Ed.); Dongyan Liu (Ed.); Yu Dong (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [In recent years, advanced nanocomposites have attracted a great deal of attention from materials engineers and industrialists due to numerous advantages, including the use of a small amount of nanofillers to significantly enhance the material properties of resulting nanocomposites, widespread applications in a range of fields, such as automobiles, aerospace and aerocrafts, building structures, biomedical devices, etc., as well as easy processibility based on current manufacturing technologies, such as melt compounding, solution casting, in situ polymerisation and electrospinning. Advanced nanocomposites reinforced with carbon nanotubes (CNTs), graphene oxides (GOs), nanoclays, nanocellulose, and nanofibres demonstrate excellent multifunctional properties, consisting of better mechanical, thermal, electrical, and barrier properties. The key issue is still the encountered challenge of homogeneous filler dispersion in morphological structures for tailored advanced nanocomposites. Hence, processing-structure-property nanocomposite relationship is crucial for their future development as innovative hybrid material systems. This Special Issue will address above-mentioned points in relation to manufacturing, characterisation, and properties of advanced nanocomposites to offer an insight into this new composite family with the incorporation of nanofillers, nanoparticles, and nanomaterials in order to eventually achieve the nanotechnological "bottom-up" scheme.